2005
DOI: 10.1177/1721727x0500300108
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Psoriasis Vulgaris with Calcipotriol Betamethasone Dipropionate Combination Followed by Calcipotriol and Assessment of the Adjuvant Basic Use of Urea-Based Emollients

Abstract: A new combination product containing betamethasone dipropionate and calcipotriol (Dovebet" ointment) has been proven very effective and well tolerated in patients with psoriasis vulgaris. Emollients are adjunctive modalities commonly used in psoriasis; however, their actual role in combination with topical drugs as well as well as their compatibility with these drugs have not been well elucidated. In 313 adult patients with psoriasis vulgaris, we studied the efficacy and tolerability of treatment with Dovobet"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Database research revealed 66 publications 7–72 on the combined use of corticosteroids and vitamin D analogues in chronic plaque psoriasis. Thirty studies were excluded because of various reasons: 10 studies were excluded because outcome reports also included systemic treatments or involved other types of psoriasis, 7–16 eight studies because outcome measures were not described or outcomes were not recorded as absolute numbers, 17–24 five because the treatment regimen was unclear, 25–29 four because the papers did not reveal original data, 30–33 two because demographic data were not described, 34,35 and one study because of inconsistent data 36 . Eight of the 36 included studies concern scalp psoriasis and will be discussed separately.…”
Section: Resultsmentioning
confidence: 99%
“…Database research revealed 66 publications 7–72 on the combined use of corticosteroids and vitamin D analogues in chronic plaque psoriasis. Thirty studies were excluded because of various reasons: 10 studies were excluded because outcome reports also included systemic treatments or involved other types of psoriasis, 7–16 eight studies because outcome measures were not described or outcomes were not recorded as absolute numbers, 17–24 five because the treatment regimen was unclear, 25–29 four because the papers did not reveal original data, 30–33 two because demographic data were not described, 34,35 and one study because of inconsistent data 36 . Eight of the 36 included studies concern scalp psoriasis and will be discussed separately.…”
Section: Resultsmentioning
confidence: 99%
“…However, the dosing method in our study was well accepted by patients. Another consideration derived from our results is that calcitriol ointment can be safely combined to background treatment with urea-based emollients which can in tum enhance the activity of drugs in psoriasis acting as 'therapeutic moisturizers' (24).…”
Section: Discussionmentioning
confidence: 97%
“…However, the percentage of affected area was not influenced [ 42 ]. From three small studies, limited evidence is known for an enhanced efficacy of other topical agents such as bifonazole, dithranol or betamethasone dipropionate and calcipotriol leading to a shortened treatment duration (see Table 3 ) [ 43 – 45 ]. In the evaluated clinical studies, a burning sensation was observed in three patients (see Table 3 ) [ 39 , 42 ].…”
Section: Resultsmentioning
confidence: 99%